Teknologi Informasi Dan Nilai Dalam Novel Cyber Ghost Karya Tasyarani Aca - Eryana Shafa Salsabila; Zakyyah Mufidah Yasmin; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The purpose of this research is to find the technology contained in literary media in accordance with the Information Systems study program. In addition, to find moral values in this novel. The genre of literary work used is Cyber Ghost novel by Tasyarani Aca in Fantasteen series published by mizan publisher. The problem raised is related to how we can use the website for positive activities. Where in the story is to solve problems using the current digital era. The method used is the hermeutic method and descriptive qualitative for the journal study data of the novel's building blocks. The value contained in the short story entitled Cyber Ghost is cooperation with others to solve problems, to determine opinions, and also to remind others of mistakes that have been made. Moral messages that can be learned are related to familiarity, ethics when educating a child, morals towards parents and how to face and solve a problem. The results in this literary work are in the form of advice that everyone sometimes has personality things that the closest people should know, strengthen the sense of friendship, and address a problem properly. The technology contained in this novel is a website which is managed by two high school students.